THE IMPACT OF APPLYING INTERNATIONAL ACCOUNTING STANDARDS ON THE QUALITY OF FINANCIAL REPORTING IN THE IRAQI COMMERCIAL BANKING SECTOR - Enas Nusrat Suleiman (Scholars Digest Publishing, 2024)
The purpose of this study is to determine the level of international accounting standards and the quality of financial reporting in Iraqi commercial banks and to determine the impact of the application of international accounting standards on financial reporting. Descriptive analysis was used and questionnaires were distributed to the study population (180) which consisted of (180) employees, assistant department heads, department heads and assistant department heads. (172) questionnaires were received. After eliminating (7) questionnaires of insufficient value and (5) questionnaires that could not be analyzed due to extremism, the total number of resolutions was (160). The study found that the level of application of international accounting standards in Iraqi commercial banks was (3,488) (score range (0-4)) and the average quality of financial reporting was (3,432) (score range (0-4)). The study also showed that the application of international accounting standards had a significant positive impact on the quality of financial reporting (comprehensibility of reports, adequacy, reliability and comparability of financial reports) in Iraqi commercial banks.
Keywords: International Accounting Standards, Quality of Financial Reporting, Commercial Banking.